PROJETO CONCEITUAL DE CONCEPÇÃO DE UM REBOQUE PARA TRANSPORTE DO VEICULO BAJA - BONFADA, ANDERSON R.; VALDIERO, ANTONIO C.; CARVALHO, DANIEL F.; KAFKA, DAVID; SCHIMIDT, FABRICIO C.; ABENTROTH, FERNANDO H.; GILAPA, GENARO M. M.; STAM, JOAO G.; BARBIERI, JOAO R. P.; CARPES, JONATAS V.; HEIMBURG, JULIO C. V.; DANETTE, LUCAS I.; et al. (Salão do Conhecimento, 2013)
Resumo